1996
DOI: 10.1007/bf01875858
|View full text |Cite
|
Sign up to set email alerts
|

History of sexual abuse and parental alcohol misuse: Risk, outcomes and protective factors in adolescents

Abstract: This study examined the school performance, suicidal involvement, disordered eating behaviors, pregnancy risk and chemical use of teenagers with a history of sexual abuse or parental alcohol misuse and found that they had higher rates of these adverse outcomes than among a comparison group of teenagers without such background risk factors. Adolescents with dual-risk background reported higher levels of suicide risk, disordered eating, sexual behaviors and chemical abuse than teenagers with only one background … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 71 publications
(60 reference statements)
2
21
0
Order By: Relevance
“…When caregiver substance abuse is present, children often suffer numerous behavioral and developmental consequences, including lower academic achievement, truancy, suicidal involvement, teenage pregnancy, eating disorders, and the use of tobacco, alcohol, and marijuana (Chandy et al 1996; Hill et al 2011). Families in which maternal substance abuse is present are more likely to experience more frequent and longer foster care placements, and are more likely to exit the foster care system through adoption (Semidei et al 2001; Vanderploeg et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…When caregiver substance abuse is present, children often suffer numerous behavioral and developmental consequences, including lower academic achievement, truancy, suicidal involvement, teenage pregnancy, eating disorders, and the use of tobacco, alcohol, and marijuana (Chandy et al 1996; Hill et al 2011). Families in which maternal substance abuse is present are more likely to experience more frequent and longer foster care placements, and are more likely to exit the foster care system through adoption (Semidei et al 2001; Vanderploeg et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This emphasis is much aligned with resilience research. Indeed, external support in the form of family, friends and the community (Chandy, Blum & Resnick, 1996) and high self-esteem (Valentine & Feinauer, 1993) have been found to be prominent protective factors by researchers.…”
Section: Reader In Social Workmentioning
confidence: 98%
“…Just as the suicide rates differ between the genders, risk and protective factors also appear to impact male and female suicide rates differently. For instance, people with a history of sexual abuse have a significantly increased rate of suicidal ideation and attempts (Benda, 2003;Chandy et al, 1996;Evans et al, 1996;Freedenthal and Stiffman, 2004;King et al, 2004;Martin et al, 2004;Osgood and Manetta, 2000-01;Rodell et al, 2003;Tubman et al, 2001;Ystgaard et al, 2004). However, Martin et al's (2004) study found the relationship between sexual abuse and suicidality among females to be completely mediated by hopelessness, depression and family dysfunction.…”
Section: Data Synthesismentioning
confidence: 99%
“…A positive relationship between the intensity and longevity of substance abuse and attempted suicide exists among homeless veterans (Benda, 2003), but this finding is in need of further study to determine whether it holds true for other populations. Alcohol abuse in the home is also positively related to suicidality among adolescents (Chandy et al, 1996;Fernquist, 2000), while among Native American adolescents, the positive relationship between suicidality and substance abuse in the home is found only among adolescents who are raised on a reservation (Freedenthal and Stiffman, 2004). A significant and positive relationship between divorce rates and suicide rates is also established for both genders and across numerous countries (Cutright and Fernquist, 2004;Fernquist, 1995-96;Fernquist and Cutright, 1998).…”
Section: Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation